The Biotoxic Effects of Ag Nanoparticles (AgNPs) on Skeletonema costatum, a Typical Bloom Alga Species in Coastal Areas - Ke Shi; Yuehong Yao; Jianliang Xue; Dongle Cheng; Bo Wang (Journal of Marine Science and Engineering, 2023)
With the rapid development of nanotechnology, nanomaterials have been widely utilized in many industries and daily life applications due to their unique properties. However, their potential release and the human health/environmental consequences have raised public concern greatly. In this study, we compared the toxic effects of AgNPs and AgNO3 on Skeletonema costatum in 10, 100, and 500 μg·L−1 Ag treatments. In all the AgNP exposure experiments, cell membrane damage and growth inhibition occurred. However, the cellular damage only obviously appears on exposure to a high concentration of AgNO3. The antioxidant enzyme (SOD and CAT) activities and lipid peroxidation in Skeletonema costatum were also induced significantly in the AgNP treatments. In addition, the percentage of Ag release in seawater increased with the increase in AgNP concentrations (13%, 32% for 100 and 500 μg·L−1 AgNPs). Thus, the biotoxic effects of AgNPs were found to be due to a combination of the solubilization of particles into toxic metal ions and the nature of the nanoparticles. It was worth noting that the induction of oxidative stress and damage to the cell membrane comprised the dominant mechanism of toxicity for AgNPs. Therefore, the behavior of nanometals in seawater affects the biotoxic effect on the phytoplankton. These results shed light on the biological toxicity of nanometals and their possible toxicity mechanism.